Ent-Kauranoids isolated from Isodon eriocalyx var. laxiflora and their structure activity relationship analyses. Issue 48 (2nd December 2015) - Wang, Wei-Guang; Yang, Jin; Wu, Hai-Yan; Kong, Ling-Mei; Su, Jia; Li, Xiao-Nian; Du, Xue; Zhan, Rui; Zhou, Min; Li, Yan; Pu, Jian-Xin; Sun, Han-Dong
Abstract: In this report, a new cytotoxic group, a 15-oxo-16α-H-17-methoxy (or ethoxy)- unit, was suggested from the structure-activity relationship analyses of 39 ent -kaurane diterpenoids, including 17 new compounds (neolaxiflorins I–Y, 1 –17 ) isolated from the leaves of Isodon eriocalyx var. laxiflora using an in vitro cytotoxicity assay against HL-60, SMMC-7721, A-549, MCF-7, and SW-480 human cancer cell lines. This discovery is counter to the rule that the α, β-unsaturated ketone (C-15-C-16-C-17) unit is indispensable for cytotoxicity of the ent -kauranoids. Furthermore, portions of the isolates exhibited inhibitory activity against nitric oxide (NO) production in LPS-activated RAW264.7 macrophages. The NF-κB inhibitory activity assay suggests a potential novel cytotoxic mechanism for compounds9 and22 . Graphical abstract: